Globalization of food and agriculture and the poor - von Braun, Joachim; Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2008)
The economic impact of globalization, particularly on poverty, and the changes in agri-food markets have received much attention in recent years. However, the intersection of these two trends has been neglected. The present volume fills this gap by focusing on the way globalization of agri-food systems affects the world’s poor and its impact on food and nutrition security in developing countries. Rather than offering a single policy prescription or simplistic messages about globalization being 'good' or 'bad', the book acknowledges the complexity of the subject by including a variety of policy and research perspectives. The contributors analyse in details the links between poverty and globalization. They examine the different interactions between the forces influencing and driving globalization—politics and governance; markets, capital investment, and labour; information and innovation; and health, social policies, and conflicts—and elements of the food chain—production, marketing, and consumption. Complementing these analyses are six interspersed essays by leading policy analysts and economists that highlight primary issues in the ongoing debate on the impact of globalization. The insights offered make this volume a valuable resource for researchers and decisionmakers in government, NGOs, and the private sector who wish to shape globalization and the agri-food system to produce pro-poor outcomes.